2021
DOI: 10.1088/2516-1091/ac1f6c
|View full text |Cite
|
Sign up to set email alerts
|

Current and emerging techniques for oral cancer screening and diagnosis: a review

Abstract: Oral cancer causes over 350 000 deaths annually worldwide. Although most cases are in Asia, the incidence of oral cancer is rising across the world. Despite recent advances in screening methods, oral cancer remains a significant cause of mortality and morbidity. The 5-year survival rate (50%–60%) has not improved over the past several decades. Early detection and accurate diagnosis of the disease can improve the survival rate and patients’ quality of life. This article provides a topical review of current and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 167 publications
0
6
0
Order By: Relevance
“…As auxiliary tools, imaging techniques have become indispensable in clinic, where image identification algorithms play an important role [ 39 ]. This study extends our prior work in oral cancer, which demonstrated the feasibility of OCT image-based identification of OSCC and normal mucosa by using optical parameters as markers to establish the optical attenuation model and using texture-based ML models [ 21 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…As auxiliary tools, imaging techniques have become indispensable in clinic, where image identification algorithms play an important role [ 39 ]. This study extends our prior work in oral cancer, which demonstrated the feasibility of OCT image-based identification of OSCC and normal mucosa by using optical parameters as markers to establish the optical attenuation model and using texture-based ML models [ 21 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with screening the entire population, a program targeting the population at high risk for some cancers can direct resources to those most likely to benefit and can potentially lead to better cost-effectiveness and lower false-positive cases . Despite fitting WHO’s criteria for a disease that screening should target, HNC screening has not been implemented in many jurisdictions due to a lack of systematic understanding on whether such a program would meet WHO’s standards, especially on enhancing survival …”
Section: Introductionmentioning
confidence: 99%
“…9 Despite fitting WHO's criteria for a disease that screening should target, 8 HNC screening has not been implemented in many jurisdictions due to a lack of systematic understanding on whether such a program would meet WHO's standards, especially on enhancing survival. [9][10][11][12][13][14][15][16][17][18] We aimed to gather international literature published between 2001 and 2022 to answer 3 questions: (1) what are common techniques used for adult HNC screening; (2) are they effective in increasing HNC detection, especially localized tumor detection; and (3) does screening improve overall and cancer-specific survival? Results of this review will provide general insights on the merits of HNC screening in addition to giving more specific guidance on whether such a program should be universal or risk targeted to meet the needs of populations with different existing prevalence of HNC.…”
mentioning
confidence: 99%
“…Abnormal changes in the structure of oral mucosa may occur due to many oral diseases, such as oral leukoplakia, erythroplakia, oral candidiasis, and oral cancer [11,12]. In clinical practice, these changes are usually assessed by visual inspection and palpation, despite their poor accuracy and subjective nature [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, these changes are usually assessed by visual inspection and palpation, despite their poor accuracy and subjective nature [9,13]. On the other hand, diagnosis of potential malignant lesions currently relies on surgically removed biopsies [12]. This invasive procedure causes pain and discomfort for the patient.…”
Section: Introductionmentioning
confidence: 99%